Artificial bee colony algorithm based self-optimization of base station antenna azimuth and down-tilt angles - Jiaqi CAI; Haibin WAN; Youming SUN; Tuanfa QIN (Dianxin kexue)
Aiming at the problem of SON coverage self-optimization proposed in 3GPP, a method based on artificial bee colony algorithm was proposed to optimize the azimuth and down-tilt angles of base station antenna at the same time.Firstly, the base station determined the area to be optimized according to the MR data reported by user equipment, and established the objective function of the average gain of the base station antenna area to be optimized.Secondly, the artificial bee colony algorithm was used to solve the objective function, and the optimal solution of the base station antenna azimuth and down-til tangle was got.Finally, the base station antenna azimuth and down-tiltangles were adjusted to the optimal value to achieve the coverage self-optimization of the base station.Through system modeling, simulation and field verification, taking the RSRP received by the user’s equipment as the index, the identification method using the artificial bee colony algorithm was improved, 6.81 dB higher than the initial parameters which were not optimized, and 4.35 dB higher than the method based on artificial experience.The experimental results show that the optimization method proposed can accurately and timely adjust the azimuth and down-tiltangles of the base station antenna according to the user distribution, and improve the signal strength received by the user equipment.